2013
DOI: 10.1016/j.seizure.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for uncontrolled seizures in adults; the impact of pseudointractability

Abstract: Uncontrolled seizures are a commonly encountered problem, especially at epilepsy clinics and one should consider all possible reasons for these uncontrolled seizures. The mainstay for making a correct diagnosis is a detailed clinical history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Choosing an optimal ASM is not an exact science and requires training and extensive experience, which may not always be available. Suboptimal ASM selection is common, at least in some settings, and may cause harm 6‐11 . Whether experts weigh critical factors in a similar way is not known, and inter‐rater agreement in selecting currently available ASMs for individuals with a wide range of clinical variables has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing an optimal ASM is not an exact science and requires training and extensive experience, which may not always be available. Suboptimal ASM selection is common, at least in some settings, and may cause harm 6‐11 . Whether experts weigh critical factors in a similar way is not known, and inter‐rater agreement in selecting currently available ASMs for individuals with a wide range of clinical variables has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying epilepsy syndrome and seizure type(s) correctly is a necessary first step in clinical practice, but it may not necessarily lead to choice of an appropriate treatment. Evidence of incorrect or suboptimal drug selection in patients with epilepsy has been documented by many studies done in different settings 9,32,33 . Our instrument has the potential to reduce inappropriate prescribing, as it provides advice not only on drug choice but also on dosage and titration schedules.…”
Section: Discussionmentioning
confidence: 99%
“…This risk is compounded by a scarcity of neurologists and epilepsy specialists in many places, particularly in low‐ and middle‐income countries, but also in wealthier countries 8 . Moreover, misdiagnosis and misclassification of seizures are common, and can lead to selection of either ineffective or potentially seizure‐aggravating treatments 9 . In one study of 350 adults with uncontrolled seizures, 29% were found to have been prescribed an inappropriate ASM and 18% were taking suboptimal ASM doses 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Juvenile myoclonic epilepsy is often characterized by excellent response to treatment, 3 but delay to a correct diagnosis and consequently, choosing an inappropriate or suboptimal agent may result in uncontrolled seizures in many patients. 6 Besides, even a correct diagnosis does not guarantee an optimal response to therapy and many patients suffer from ongoing Table 1 Comparison of demographic and clinical characteristics of patients with JME, with or without seizures in their follow-up. seizures despite an appropriate treatment plan.…”
Section: Discussionmentioning
confidence: 99%